Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan - Aini, Hayu Latifah; Rofiqoh, Ifah (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to systematically examine the influence of motivation and work environment on employee performance in the last five years (2020–2025). In an era of increasingly competitive global competition, organizations are required to manage their human resources effectively. Internal and external motivation factors as well as the quality of the work environment are the main determinants of employee performance achievement. This study uses a Systematic Literature Review (SLR) approach by reviewing 30 articles from various scientific databases, including Scopus, ScienceDirect, and accredited national journals. The results of the study show that motivation, both intrinsic and extrinsic, as well as a physically and psychologically supportive work environment have a significant influence on performance improvement. In addition, it was also found that mediating variables such as job satisfaction and employee engagement strengthened the relationship between motivation and work environment on performance. These findings provide theoretical contributions in the field of human resource management as well as practical implications for organizations in designing performance improvement strategies.